Clinical Evaluation of Ranitidine and Omeprazole in Shortening Hospital Stay for Dyspepsia Patients - Hartanti, Riana; Manalo, Andres; Zikri, Muhammad (Media of Health Research, 2025)
Dyspepsia is a common complaint of the upper gastrointestinal tract that often leads to a decrease in quality of life and increased healthcare burden. Two drugs commonly used in the treatment of dyspepsia are ranitidine, an H2 receptor antagonist, and omeprazole, a proton pump inhibitor. This study aims to evaluate the clinical effectiveness of ranitidine and omeprazole in reducing the length of treatment for dyspepsia patients. The study uses a quantitative method with a retrospective approach to the medical record data of inpatient dyspepsia patients at a hospital in Indonesia. The sample consisted of two groups of patients, each receiving ranitidine and omeprazole therapy. Analysis was performed on treatment duration, symptom improvement, and adverse events. The results showed that patients receiving omeprazole had a more significant reduction in average treatment duration compared to the ranitidine group. Furthermore, omeprazole had better tolerability with fewer side effects. These findings indicate that omeprazole is more clinically effective in accelerating the recovery of dyspepsia patients compared to ranitidine. This study provides a scientific basis for medical practitioners in choosing optimal therapy for dyspepsia, especially in the context of healthcare efficiency. Further research with a prospective design is needed to strengthen these findings.